The Mythological Methodology and its Application to Pre-Islamic Poetry - Ghaitha Kadra (دراسات فی اللغه العربیه و آدابها)
This research deals with the application of the mythological method to pre-Islamic poetry which includes mythological images and legendary dimensions resulting from the imagination of the pagan poets and aesthetically interwoven with the linguistic structures. The research also aims to underline the efficiency of the mythological method for analyzing poetic texts and revealing their mythological dimensions created by the poet's imagination, in chronological stages. Illustrated by poetic texts we depic these stages in the pagan poetry as follows:Â  1. departure 2. journey and loss 3. searching for indentity The aim of this research is to present the my thological and philosophical aspect of the images which convey the poetic sense and to determine the validity of the application of this method on the pagan poetry.